Frei, fair und lebendig Die Macht der Commons - Helfrich, Silke (Sozialtheorie, 2019)
This book should give you courage. It unites meaningful thinking with a new way of acting. The goal: a free, fair and lively society. But the familiar has become deeply engraved in our minds, in our everyday lives, in the market and the state. Silke Helfrich and David Bollier reveal traditional ways of thinking and design a program for successful coexistence, a different understanding of politics and caring business. The focus is on commons practices. They show how we pursue common goals in diversity. Practically, houses and vehicles can be created in a similar way to Wikipedia. The book also suggests how to think like a "commoner". It offers a language for the world of tomorrow. It's not just changing the economy and politics - it's changing us.